Method of evaluation of fuel losses through evaporation - Бойченко C. B. (Proceedings of National Aviation University (archive), 1999)
In order to evaluate fuel losses through evaporation it is important to correctly select the evaluation method of losses through evaporation. The existing methods have been analysed. Among them the method of dynamic evaporability by blowing through the fuel sample a tenfold volume of air - the method of direct comparison of the samples. Also the optical properties of fuel were investigated. Developing the idea of refractometric method of evaluation of losses through evaporation, we propose a complex method based on graphical and refractometric ways of losses evaluation